Abilities of Tomatoes (Solanum lycopersicum) as Bait in a Rat Trap - Al Azhari, Muhammad Fuady; Noraida, Noraida; Santoso, Imam; Erminawati, Erminawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
Rats are rodents that harm humans and carry diseases, so it is necessary to control rats by using bait traps to trap rodents. The community commonly uses dried fish as bait, but the nature of rats necessitates other variations. s. The purpose of using tomatoes was to determine the ability of tomatoes and dried fish to act as bait in rat traps. This type of research uses a quasi-experiment. This study employed the post-test-only control group design method, implementing three bait installation treatments: tomato, dried fish, and control. We conducted this research at the Bauntung market in Banjarbaru, repeating it 27 times with three treatments: tomato bait, dried fish, and no bait. The statistical tests revealed no significant difference in the average number of rats trapped in the bait between tomatoes and dried fish. This was because the number of mice trapped between tomato bait and dried fish bait did not show a significant difference. We expect the results of this study to provide valuable suggestions for Bauntung Market managers and future researchers on rat control using tomato bait traps.